S17 Ivacaftor treatment in patients 6 to <12 months old with cystic fibrosis with a CFTR gating mutation: results of a 2-part, single-arm, phase 3 study. (12th November 2019) - Davies, JC; Wang, LT; Panorchan, P; Campbell, D; Tian, S; Higgins, M; Egbuna, O; McKee, C; Rosenfeld, M
Abstract : Objectives: ARRIVAL (NCT02725567 ) is a single-arm, Phase 3 study of the pharmacokinetics (PK) and safety of ivacaftor (IVA) in patients aged <24 months with cystic fibrosis (CF) with ≥1 CFTR gating mutation. We present results of the completed 6- to <12-month cohorts. The study is ongoing for patients aged <6 months. Methods: Patients received IVA (5 to <7 kg, 25 mg; 7 to <14 kg, 50 mg) every 12 hours for 4 days in part A (A) and 24 weeks in part B (B). Primary endpoints were PK (A) and safety (A, B), including serum lipase and amylase. Secondary/exploratory endpoints (B) included PK and changes in sweat chloride (SwCl), growth, serum immunoreactive trypsinogen (IRT) and faecal elastase (FE-1). Results: A and B enrolled 6 and 11 patients; mean age (standard deviation [SD]) was 7.7 (1.9) and 9.0 (1.3) months, respectively. PK from 4 days of IVA dosing in A informed dosing in B, in which exposure was consistent with that observed in adult patients. IVA was generally safe and well tolerated in both parts. In A, one patient had adverse events (AEs) (constipation, vomiting and sleep disorder) considered to be related to study drug. There were no deaths, serious AEs (SAEs) or AEs leading to study drug interruption or discontinuation. In B, one patient had increased alanine aminotransferase (>3 to ≤5 × upper limit of normal) that normalised with continued dosing; three patients reported SAEs (none were deemed related to IVA). Improvements were seen in multiple efficacy endpoints (table 1). Conclusion: These results suggest that IVA can be dosed safely in patients aged 6 to <12 months; substantial improvements in SwCl indicate improved CFTR function. Increases in FE-1 and reductions in lipase and IRT suggest there is a window of opportunity in early life for improving pancreatic function. These findings are consistent with those in children aged 12 to <24 months treated with IVA and support treating the underlying cause of CF in infants with IVA. Sponsor: Vertex Pharmaceuticals Incorporated.